2019
DOI: 10.1002/ece3.5536
|View full text |Cite
|
Sign up to set email alerts
|

Drought affects the coordination of belowground and aboveground resource‐related traits in Solidago canadensis in China

Abstract: Quantifying patterns of variation and coordination of plant functional traits can help to understand the mechanisms underlying both invasiveness and adaptation of plants. Little is known about the coordinated variations of performance and functional traits of different organs in invasive plants, especially in response to their adaptation to environmental stressors. To identify the responses of the invasive species Solidago canadensis to drought, 180 individuals were randomly collected from 15 populations and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
(99 reference statements)
1
10
1
Order By: Relevance
“…Unlike in other studies (e.g. Larson & Funk 2016; Du et al 2019), we did not find more or stronger trait correlations in our drought treatment compared to control. Rather, we found relatively consistent trait relationships across both developmental stages and treatments levels.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike in other studies (e.g. Larson & Funk 2016; Du et al 2019), we did not find more or stronger trait correlations in our drought treatment compared to control. Rather, we found relatively consistent trait relationships across both developmental stages and treatments levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, potential negative impacts of using cultivars raise additional concerns about their ubiquitous use in restoration. Studies have found that the process by which native materials are selected and produced may result in unintentional selection for nonadaptive traits (Espeland et al 2017) or lower variability in traits (Foxx & Kramer 2020). In addition, their introduction into sites with conspecifics may negatively affect the genetic integrity of local populations (Hufford & Mazer 2003).…”
Section: Relationships Among Traits and Trait Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf nitrogen content is closely related to photosynthesis and relative growth rate of plants. The leaf nitrogen content in long-term grazing exclusion of Stipa brevi ora is higher than grazing, indicating that leaf nitrogen content is positively correlated with environmental factors (Du et al 2019;Wang et al 2016). In the study, we also found that leaf functional traits in non-linear trend (Sandel et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were noted in one preceding research where a high soil water holding capacity had significant effect on the growth and biomass of Solidago canadensis . [ 47 ] We thus noted that invasive A. philoxeroides has a high survival rate, and because of it, it is expected to grow better with increasing availability of resources like water and nutrients. The current findings also supported our hypothesis regarding the effect of water availability on the functional traits of plants (PH, LA, RL, TFBm, and TDBm) that were significantly related with the performance of plants.…”
Section: Discussionmentioning
confidence: 99%